Atomic scale modelling of the cores of dislocations in complex materials part 2: applications - Gale, Julian; Wright, Kathleen; Walker, A.; Slater, B. (Royal Society of Chemistry, 2005)
This study investigates the behaviour of selected, morphologically important surfaces of dolomite (CaMg(CO3)2), using computational modelling techniques. Interatomic potential methods have been used to examine impurity substitution at cationic sites in these surfaces. Environmentally prevalent cations were studied to this end, namely Ni21, Co21, Zn21, Fe21, Mn21 and Cd21, all of which are also found as end-member carbonate minerals. Solid?solution substitution was investigated and showed that Cd and Mn will substitute from their end-member carbonate phase at either dolomite cation site. Mn is found to preferentially substitute at Mg sites, in agreement with experimental findings. For Ni21, Co21 and Zn21, the magnitude of substitution energies is approximately equal for all surfaces, with the exception of the (1014) surface. However, for the larger cations, a far greater disparity in substitution energies is observed. At a stepped surface, analogous substitutions were performed and it was found that substitution energies for all impurity cations were reduced, indicating that uptake is more viable during growth. The predominant surface, the (1014), was solvated with a monolayer of water in order to investigate the influence of hydration on substitution energetics. The addition of water changes the relative preference for substitution of the different cations. Under aqueous conditions, the substitution energy is determined by three competing factors, the relative importance of which cannot be predicted without this type of computational investigation.